DESIGN OF A MODERN FASTENING AND LOOSENING DEVICE FOR MACHINING OF PLATE-TYPE PARTS ON A MILLING MACHINE - Abdullayeva, Dona Toshmatovna (Educational Research in Universal Sciences, 2022)
In the course of the study, an analysis of the manufacturability of the part was carried out. The type of production was determined in accordance with the annual production program and the design of the part. In accordance with the type of production, as well as the material of the part, a blank was selected. Calculations of allowances, tolerances, technological dimensions, cutting modes, main and auxiliary times, work piece clamping force for milling have been carried out. As a result of the study, a technological process for manufacturing a part was designed and a special device for milling was designed.